Session Topic: International Trade and Finance: Balance of Payments and International Investment: Discussion - Junz, Helen B. (Journal of Finance, 1974)
Helen B. Junz, Session Topic: International Trade and Finance: Balance of Payments and International Investment: Discussion, The Journal of Finance, Vol. 29, No. 2, Papers and Proceedings of the Thirty-Second Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1973 (May, 1974), pp. 680-682